Fostering a ‘Rahmah’ (Mercy) Environment: An Inclusive Learning Model for Students with Special Needs in Islamic Primary Schools - Loso Judijanto; Ahmed Al-Harthy; Mariam Al-Mashani; Nasser Al-Hosni (Islamic Studies in the World, 2025)
This study explores the development of an inclusive learning model grounded in the Islamic value of rahmah (mercy) to support students with special needs in Islamic primary schools. The research is situated within the growing concern that many Islamic schools emphasize cognitive achievement and religious ritual proficiency while lacking structured frameworks that address the diverse developmental, emotional, and cognitive needs of children with disabilities. The concept of rahmah, rooted in Qur’anic and prophetic traditions, provides a powerful ethical foundation for rethinking inclusion as a moral, pedagogical, and communal responsibility rather than a technical intervention. The study aims to design and examine a rahmah-based inclusive learning model that integrates Islamic ethical principles with contemporary special education practices. A qualitative design was employed, combining document analysis of Islamic educational guidelines, observation of classroom practices in three Islamic primary schools, and semi-structured interviews with teachers, parents, and inclusion coordinators. Data were analyzed using thematic coding to identify pedagogical, emotional, and organizational components of rahmah-driven inclusion. The findings reveal that an effective rahmah environment requires three core elements: compassionate teacher-student interaction rooted in empathy and dignity; differentiated instructional practices aligned with students’ abilities; and a supportive school culture that normalizes diversity through collaborative roles among teachers, peers, and families. Schools implementing these elements reported improvements in student engagement, emotional security, and social participation among learners with special needs.